THE EFFECT OF WORK EXPERIENCE, WORK ACHIEVEMENT, EDUCATION AND TRAINING ON CAREER DEVELOPMENT IN PT. PLN (PERSERO) KOTA PADANG RAYON KURANJI - Ai Elis Karlinda; Putri Azizi; Mardhatila Fitri Sopali (Journal of Information System, Applied, Management, Accounting and Research, 2021)
This study aims to determine how much influence the work experience, work performance, education and training have on the career development of employees at PT PLN (Persero) Rayon Kuranji, Padang City. The analytical method used is correlation analysis and multiple regression. The data collection method in this study is to use a questionnaire filled out by respondents, namely employees at PT PLN (Persero) Rayon Kuranji, Padang City. From the results of multiple regression analysis, it shows that: (a) work experience has a partially significant effect on career development, (b) work performance has a partially significant effect on career development, (c) education has a partially significant effect on career development, (d) training does not have a partially significant effect on career development, (e) work experience, work performance, education and training have a significant effect on career development together, (e) the contribution of variable work experience, work performance, education and training together The career development is 52.5%, while the remaining 47.5% is influenced by other variables not examined in this study.